Peningkatan Kualitas Mikrobiologi Susu Kambing Etawa (Capra Aegagrus Hircus) dengan Pemberian Xilooligosakarida (Xos) Dari Jerami - Nadia Alif Nurul Hidayah (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2026)
This study aims to determine the effect of xylooligosaccharides (XOS) on the number of LAB and Escherichia coli in Etawa goat milk. Xylooligosaccharides are the result of enzymatic hydrolysis of endo-β-1,4-D-xylanase from Saccharomyces cerevisiae BJ1824 with straw xylan substrate. The results of characterization by HPLC showed that the XOS produced was dominated by xylotriose (X3) with a concentration of 2.68 mM. XOS application was carried out on Etawa goats at a dose of 2% for 30 days and milk samples were taken on days 9, 16, 23, and 30. The number of LAB and E.coli in Etawa goat milk was determined using the Total Plate Count (TPC) method. The results showed that administration of 2% XOS was able to increase the number of LAB in milk and suppress the growth of E. coli compared to the control group. The results of administering XOS 2% on the 30th day were able to increase the number of BAL in Etawa goat milk by 4.5 × 10^5 (CFU/mL) and suppress the growth of E. coli by 1 × 10^2 CFU/mL. The highest number of BAL was in the administration of XOS 2% on the 30th day of 4.5 × 10^5 (CFU/mL). The number of E. coli in the treatment group tended to be lower than the control at 1 × 10^2 CFU/mL. exhibiting characteristics typical of LAB: Gram-positive bacteria and catalase-negative. exhibiting characteristics typical of E.coli: Gram-negative bacteria and catalase-positive.
Approved by Teddy
Keywords: Etawa goat milk; Escherichia coli; prebiotic; lactic acid bacteria; Total Plate Count; xylooligosaccharides.